Heat activation mechanism of TRPV1: New insights from molecular dynamics simulation. Issue 2 (3rd April 2019) - Zheng, Wenjun; Wen, Han
ABSTRACT: As a member of the transient receptor potential (TRP) channels superfamily, the TRPV1 channel undergoes a closed-to-open gating transition in response to various physical and chemical stimuli including heat. Thanks to recent progress in cryo-electron microscopy, high-resolution structures are becoming available for various TRP channels including TRPV1. This has enabled us to study the molecular mechanism of TRPV1 channel gating by using molecular simulation. Here we review recent progress in molecular simulations of TRPV1 channel by us and others, with focus on our molecular dynamics (MD) simulations of TRPV1 at different temperatures. While no consensus has been reached on the heat activation mechanism of TRPV1, the simulations have offered specific predictions and models for future experimental studies to test.